Diversity of Ehrlichia spp., Anaplasma spp. and Neorickettsia spp. in vampire bats - de Mello, Victória Valente Califre [UNESP] (2024)
Although bats (Mammalia: Chiroptera) act as natural reservoirs for many zoonotic pathogens around the world, few studies have investigated the occurrence of Anaplasmataceae agents in bats, especially vampire bats. The family Anaplasmataceae (order Rickettsiales) encompasses obligate intracellular bacteria of the genera Anaplasma, Ehrlichia, Neorickettsia, Neoehrlichia, Wolbachia, and Allocryptoplasma. The present study aimed to investigate, using molecular techniques, the presence of species of Anaplasma, Ehrlichia, and Neorickettsia in vampire bats sampled in northern Brazil. Between 2017 and 2019, spleen samples were collected from vampire bats belonging to two species, Desmodus rotundus (n = 228) from the states of Pará (n = 207), Amazonas (n = 1), Roraima (n = 18) and Amapá (n = 3), and Diaemus youngii (n = 1) from Pará. Positivity rates of 5.2% (12/229), 3% (7/229), and 10.9% (25/229) were found in PCR assays for Anaplasma spp. (16S rRNA gene), Ehrlichia spp. (dsb gene) and Neorickettsia spp. (16S rRNA gene), respectively. The present study revealed, for the first time, the occurrence of Anaplasma spp. and different genotypes of Ehrlichia spp. in vampire bats from Brazil. While phylogenetic analyses based on the dsb and ftsZ genes of Ehrlichia and 16S rRNA of Anaplasma spp. revealed phylogenetic proximity of the genotypes detected in vampire bats with Anaplasmataceae agents associated with domestic ruminants, phylogenetic inferences based on the gltA and groEL genes evidenced the occurrence of genotypes apparently exclusive to bats. Neorickettsia sp. phylogenetically associated with N. risticii was also detected in vampire bats sampled in northern Brazil.